Bitka katoličkog pravaštva protiv interkonfesionalnog zakona, recenzirani rukopis - Strecha, Mario (2005)
Bitka katoličkog pravaštva protiv interkonfesionalnog zakona, recenzirani rukopis
Projekt MZOS
HRV